Blending Work Values, Engagement, and Satisfaction to Drive OCB in Technopreneurial Startups - Meria, Lista; Hidayat, Syamsul; D. Santiago, Nila; Saukani, Saukani; Husnul Khotimah, Sita (Pandawan, 2024)
In startup companies, financial and other resources are often still limited, so human resources are a valuable asset that plays a crucial role in running an entrepreneur. Organizational Citizenship Behaviors (OCB) support new companies or startups success and growth. OCB can increase efficiency and productivity, create a positive work environment, and improve the ability to adapt to change. Therefore, startup companies must encourage and foster OCB among employees to achieve sustainable competitive advantage. This research analyzes the factors influencing OCB by exploring the role of work values, engagement, and job satisfaction. The participants in this research were 351 employees of startup companies in Jakarta. The sampling technique uses simple random sampling, and data analysis uses SEM-PLS. The research findings state that work values positively impact engagement and job satisfaction. Then, work engagement and job satisfaction were ultimately proven to increase employee OCB in startup companies. This study enriches the literature, especially in managing human resources in organizations, and becomes a basis for companies to create rules and policies to increase OCB in a dynamic and competitive business.